Magnetic modification of GaSe monolayer by absorption of single Fe atom. Issue 8 (16th January 2017) - Lu, Yihong; Ke, Congming; Fu, Mingming; Lin, Wei; Zhang, Chunmiao; Chen, Ting; Li, Heng; Kang, Junyong; Wu, Zhiming; Wu, Yaping
Abstract : Fe adsorbed GaSe monolayers are studied systematically using density functional theory. A strong orbit coupling effect between Fe and the vicinal Ga and Se atoms results in a half-metallicity with a 100% spin polarization. Abstract : Group-IIIA metal-monochalcogenides have attracted increasing interests due to their optoelectronic and spin electronic properties. Achieving the modification of their magnetism is desirable for device applications. In our work, structural, electronic, and magnetic properties of the Fe adsorbed GaSe monolayer are studied systematically using density functional theory (DFT). It is found that there is a strong orbit coupling effect between Fe and the vicinal Ga and Se atoms, resulting in a half-metallicity with a 100% spin polarization. The magnetic moments of the nearest neighbour Ga and Se atoms are −0.004 μ B and −0.178 μ B, respectively, demonstrating an antiferromagnetic coupling with the adsorbed Fe atom. Meanwhile, the induced majority and minority spin states are inclined to distribute on the Se and Ga atoms separately. The hybridization of Fe-3d, Se-4p, and Ga-4p orbitals is responsible for the induced magnetic moments and spin polarization in the nonmagnetic GaSe monolayer. These investigations shed light on understanding the electronic and magnetic properties of the ferromagnetic/GaSe adsorption system, which offer some references for the design and construction of two-dimensional spin nanostructures.